PERMUKIMAN EMPLASEMEN PABRIK GULA PURWOREJO (1910-1933) - Lengkong Sanggar Ginaris (Balai Arkeologi Yogyakarta, 2018)
One of the sugar industries in Java is PG Purworejo, which was built in 1910. Near the PG Purworejo emplacement, there are settlements for factory employees. Although there have been many archeological studies about sugar mills, but deeper study of the existence of employee settlements still few. This study aims to reconstruct the PG Purworejo emplacement settlement from 1910 to 1930. The data used in this research is in the form of all material objects or physical data left from PG Purworejo and other related data such as old archives and photos. Data that has been collected and selected, then will be decrypted, processed to be identified and then interpreted based on the theoretical framework. Altough the remains of PG Purworejo's emplacement settlements is low, but the settlement layout can still be traced based on old photo data. The results of this study show that the emplacement settlement of PG Purworejo uses the concept of industrial settlements, where employee settlements are built near industrial sites. In addition to the concept of industrial cities, the concept of colonial settlements was also applied which was marked by the separation between European workers' settlement blocks and indigenous workers.